RESPONS PERTUMBUHAN DAN PRODUKSI KENTANG MEDIANS TERHADAP PEMUPUKAN NPK DI KELURAHAN RURUKAN PROPINSI SULAWESI UTARA - Lydia Elisabeth Agatha Tulung; Arthur G. Pinaria; Jailani ., Husain (Sam Ratulangi University, 2021)
This study aimed to analyze the response of growth and production of Median potatoes to the application of various doses of Phonska NPK fertilizer in Rurukan Village, North Sulawesi Province. This research was conducted from August to November 2020 in Rurukan Village, East Tomohon District, Tomohon City. The design used was a Randomized Completely Blocked Design (RCBD) with six (6) treatments and three (3) replications consisting of P1 Fertilization Treatment (150 kg/ha), P2 NPK Fertilization Treatment (300 kg/ha), P3 NPK Fertilization Treatment (450 kg/ha), P4 NPK Fertilization Treatment (600 kg/ha), P5 NPK Fertilization Treatment (750 kg/ha) and P6 NPK Fertilization Treatment (900 kg/ha). The results showed that (1) the treatment with Phonska NPK fertilizer at a dose of 450 kg/ha had a significant effect on the growth and production components of the Medians potato plant in Rurukan Village, North Sulawesi Province and (2) the highest plant productivity was obtained in the treatment of Phonska NPK fertilizer with dose 450 kg/ha = 18, 11 tons/ha.